Climate Risk and Beliefs in New York Floodplains - Matthew Gibson; Jamie Mullins (Institute of Labor Economics (IZA), 2020)
Applying a difference-in-differences framework to a census of residential property transactions in New York City 2003-2017, we estimate the price effects of three flood risk signals: 1) the Biggert-Waters Flood Insurance Reform Act, which increased premiums; 2) Hurricane Sandy; and 3) new floodplain maps reflecting three decades of climate change. Estimates are negative for all three signals and some are large: properties included in the new floodplain after escaping flooding by Sandy experienced 11 percent price reductions. We investigate possible mechanisms, including selection of properties into the market and residential sorting. Finding no evidence for these, we develop a parsimonious theoretical model that allows decomposition of our reduced-form estimates into the effects of insurance premium changes and belief updating. Results suggest the new maps induced belief changes comparable to those from insurance reform.
Keywords: Q54; Q58; R30; G22; 330; beliefs; updating; climate change; flood risk